Evolution of NK-mediated target recognition under the pressure of physiologic or pathologic stimuli - Miguel Lopez-Botet (Frontiers Research Topics, 2015)
Since their discovery NK cells have come out as potential tools to fight cancer and viruses. This finding early urged different groups to study the mechanisms governing NK cell function. The identification of the MHC-I-specific inhibitory receptors (i.e. KIRs, NKG2A and certain Ly49 molecules) allowed defining rather rapidly how NK cells could avoid self-aggression and how they could be directed towards targets that were forced, by viral infection or tumor transformation, to down-regulate MHC-I expression. In a second time, also the repertoire of surface activating receptors addressing NK cytotoxicity towards tumors and pathogens was mostly defined. In spite of the first findings, however, most recent studies may suggest that NK cells and their receptors might not have been evolved to kill tumor targets and, perhaps, they might have been only partially influenced, in their evolution, by the need of recognizing viruses. Indeed certain NK receptors known to activate NK cell cytotoxicity (NKp30, DNAM-1, NKp80) can also participate at regulatory interactions occurring between NK and myeloid cells. In addition, a peculiar NK cell subset which intensively populate decidua during the first trimester of pregnancy, through the engagement of specific receptors and the interaction with decidual DC, produce chemokines and pro-angiogenic cytokines, and induce Tregs. Thus, in this context, NK cells favor decidua vascularization and development of the (semiallogeneic) foetus in a tolerant environment. Viruses have nevertheless played an important role in shaping the NK cell receptor repertoire. Several studies have unveiled clues of the evolutionary struggle between these pathogens and NK cells. Different NK receptors, including NKp46, NKp30, NKp44, NKG2D, NKG2C, Ly49, and certain KIRs have been demonstrated to recognize virus-encoded or virus-induced ligands. The expression of TLR specifically recognizing microbial products, together with the unexpected role of KIR3DL2 in shuttling these products to TLR-containing endosomes have also been documented in NK cells. On the other side, different viral immune evasion molecules have been shown to interfere with the expression of ligands for T or NK cell activating receptors. In addition, viral infections can occur in the reproductive stage of life cycle, and may represent a serious threat for the species propagation. Thus the control of viruses, together with the maintenance of foetus during pregnancy, should represent major evolutionary forces in shaping NK-receptors. Along this line, the NK-mediated control of tumors should not be under the same evolutionary pressure, as tumors mostly appear later in the life cycle, and the recognition of tumor-encoded ligands may be less efficient (as the NK cell receptors might have not been selected for such aim). This may be the reason why, although displaying strong antitumor activity in vitro, NK cells could hardly contain tumor burden in vivo. In addition the pathogen-driven evolution of NK cell function may also favor the role of NK cells in the insurgence of immune-mediated diseases. This research topic will collect contributions that may clarify the relationships between the evolution of the NK receptors and their role in an efficient recognition of viruses and tumor cells or in immune-mediated diseases.